2010
DOI: 10.1002/adfm.201001243
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Properties of Micro/Nanostructured Crystallites with High‐Energy Surfaces

Abstract: Recently, special attention has been paid to the syntheses of micro/nanostructured crystallites with high-energy crystal facets, because high-energy crystal surfaces usually exhibit fascinating surface-enhanced properties and have promising applications in catalysis, photoelectrical devices, and energy conversion, etc. With particular emphasis on the results obtained by the authors' research group, this feature article gives a brief review of recent progress in the field of surface/morphology controlled synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
158
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 241 publications
(162 citation statements)
references
References 154 publications
(191 reference statements)
2
158
0
2
Order By: Relevance
“…Several insightful review papers have reported experimental and theoretical calculation studies on the important aspects that govern crystal shape modulation in semiconductors. [47][48][49][50] …”
Section: Theoretical Procedures and Computational Methodsmentioning
confidence: 99%
“…Several insightful review papers have reported experimental and theoretical calculation studies on the important aspects that govern crystal shape modulation in semiconductors. [47][48][49][50] …”
Section: Theoretical Procedures and Computational Methodsmentioning
confidence: 99%
“…Several insightful review papers have reported experimental and theoretical calculations on the important aspects that govern crystal shape modulation in semiconductor and metal NPs [78][79][80]. In addition to the thermodynamic driving forces, kinetics also plays an important role in the determination of the morphology under real growth conditions.…”
Section: = -mentioning
confidence: 99%
“…It is obvious that other peaks are much weaker than (1 1 0) di®raction peaks, which indicates that the composites tend to grow along the (1 1 0) orientation. 39 They form very thin slabs which can be further proved by the SEM and BJH images. As shown in Fig.…”
Section: Structural and Morphological Characterizationmentioning
confidence: 85%